2015
DOI: 10.1080/10916466.2015.1007383
|View full text |Cite
|
Sign up to set email alerts
|

A Laboratory Investigation on the Rheological Properties of Aged and Unaged Organic Wax Modified Asphalt Binders

Abstract: Different proportions of Sasobit (Sasol Wax, Hamburg, Germany) content were blended with 60-70 penetration grade asphalt binder type and were subjected to physical and rheological tests in order to determine the influence of Sasobit on asphalt binder. The test results indicated that Sasobit had different effects on temperature susceptibility of binders. Frequency sweep test showed that binders containing Sasobit had higher complex modulus compared to the control binders. In addition, lower phase angle values w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…It was to determine the feasibility of utilizing the local Malaysian industrial and by-products wastes such as steel slag, ceramic waste, coal fly ash, limestone, and rejected ceramic raw material as mineral fillers [4]. Research by others showed how strength of additives named Chained Interlocked Plastic Beads (CIPB) can positively reduce fatigue and rutting in Stone Mastic Asphalt (SMA) mixtures [5].…”
Section: Introductionmentioning
confidence: 99%
“…It was to determine the feasibility of utilizing the local Malaysian industrial and by-products wastes such as steel slag, ceramic waste, coal fly ash, limestone, and rejected ceramic raw material as mineral fillers [4]. Research by others showed how strength of additives named Chained Interlocked Plastic Beads (CIPB) can positively reduce fatigue and rutting in Stone Mastic Asphalt (SMA) mixtures [5].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the complexity of the pavement damage phenomenon, using proper additives and modifiers is considered the most cost-effective technique for prolong the pavement service life [8]. The modification of asphalt binder with polymeric materials and rubber powder is among the most common methods to improve the performance of the asphalt binder against most types of distresses [9,10,11]. The other method for prolonging the pavement service life is the addition of alternative environmental friendly materials.…”
Section: Introductionmentioning
confidence: 99%